Sustentabilidade em uma universidade no contexto da Amazônia Brasileira: histórico, percepções, indicadores e avaliação - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
Universities, faced with the new sustainability paradigm, are spaces that encourage change and make development models for society. Thus, the concept of higher education institutions (HEIs) that incorporate sustainable practices and habits in their policy and management has become a strong desire of these institutions, thus, there is a growth in several studies on sustainability in university environments. However, given the social, economic and physical-biotic specificities of each country and within a single country, as in Brazil, the configurations and performance of the sustainability tripod must be applied within a reality, whose sustainable development (SD) is subject local and/or regional specificity. From a regional perspective, should one reflect on what a Sustainable University (US) should be like, which can reflect the socio-environmental and economic context of the Brazilian Amazon region? Thus, the objective of this thesis is to identify and analyze the aspects, practices, indicators, and criteria that may be more relevant to the design of a HU in the region, based on the case study of a federal public university located in the interior of the Brazilian Amazon. For this, methodological procedures were used, which culminated in the composition of four articles: the first is a comprehensive review of the literature that verified and analyzed the world events that drove and started the conceptual model of SU, this influence in Brazil and implications in the HEIs of Amazon; the second identified sustainable practices at Ufopa and verified the internal community's perception of them; the third extracted indicators from Ufopa, obtaining its position in a global sustainability ranking and its position, of an experimental nature, in the national context; and the fourth presents an analysis of the strategic role of Ufopa's sustainability plan, through the Strategic Environmental Assessment (SEA) approach. The main results obtained show that: Ufopa performs sustainable practices and has an institutional commitment to the DS, but configured itself in a more distant position in a global sustainability classifier; the academic community seeks to promote ecological, socio-cultural processes and participatory dialogues; Ufopa's sustainability management must meet criteria and strategic actions aimed at Governance/Policies, Teaching/Research/Extension, People and Operational Management
Keywords: Universidade Sustentável; Desenvolvimento Sustentável; Ensino público superior; Ufopa; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSPECÇÃO NA AMAZÔNIA; SOCIEDADE, NATUREZA E DESENVOLVIMENTO